2011
DOI: 10.1002/qua.22577
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of vanadyl (IV) complexes with low molecular mass ligands: Picolinate, oxalate, malonate, and maltolate

Abstract: The insulin-mimetic activity of the VO 2þ complexes are much related to its chemical speciation in the blood serum. Low molecular mass ligands must have an important role in the mechanism of the VO 2þ biological activity affecting directly its absorption efficacy. In the present work, the chemical speciation of vanadyl (VO 2þ ) with malonate, maltolate, oxalate and picolinate ligands has been investigated by means of DFT/PCM calculations. Metal/Ligand 1:1 and 1:2 complexes have been calculated. All tautomers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Indeed, it has been the subject of many studies (Abreu et al, 2006(Abreu et al, ,2008Guimarães et al, 2007b;Noronha et al, 2007;Rodrigues et al, 2011). However, in the case of the arsenous acid, at the pH range used at the experiments, the predominant species is fully protonated H 3 AsO 3 , (pKa $9).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been the subject of many studies (Abreu et al, 2006(Abreu et al, ,2008Guimarães et al, 2007b;Noronha et al, 2007;Rodrigues et al, 2011). However, in the case of the arsenous acid, at the pH range used at the experiments, the predominant species is fully protonated H 3 AsO 3 , (pKa $9).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed speciation has been checked by means of a computational modelling. Various DFT studies concerning vanadyl coordinated by oxygenated ligands have been reported [16,33,34], and results were obtained by employing different hybrid functional and basis set. We have set up the computational method by examining the well-known aqua-vanadyl complex, both in the form of [VO(H 2 O) 5 ] 2+ , with four equatorial and one axial water ligand, and [VO(H 2 O) 4 ] 2+ system, with only equatorial ligands.…”
Section: Set Up Of the Computational Methodsmentioning
confidence: 99%
“…In the recent past computational methods based on density functional theory (DFT) has been widely used. The results of many studies have indicated that density-functional theory (DFT) is a powerful method for predicting the geometry of vanadium compounds [37][38][39][40][41][42][43]. It is a useful method for the investigation of large molecules as well [44].…”
Section: Introductionmentioning
confidence: 99%